Constraining the Impact of Dust‐Driven Droplet Freezing on Climate Using Cloud‐Top‐Phase Observations. Issue 11 (10th June 2021) - Villanueva, Diego; Neubauer, David; Gasparini, Blaž; Ickes, Luisa; Tegen, Ina
Abstract: Despite advances in our understanding of ice‐nucleating particles, the effect of cloud glaciation on the Earth's radiation balance has remained poorly constrained. Particularly, dust ice nuclei are believed to enhance cloud glaciation in the Northern Hemisphere. We used satellite observations of the hemispheric and seasonal contrast in cloud top phase to assess the dust‐driven droplet freezing in a climate model. The required freezing efficiency for dust ice nuclei suggests that climate models glaciate too few clouds through immersion droplet freezing. After tuning, the model leads to more realistic cloud‐top‐phase contrasts and a dust‐driven glaciation effect of 0.14 ± 0.13 W m −2 between 30°N and 60°N. Observations of cloud‐top‐phase contrasts provide a strong constraint for ice formation in mixed‐phase clouds and may provide a weak constraint for the associated impact on radiation and precipitation. Future studies should therefore consider both the mean‐state cloud‐phase partitioning and cloud‐phase contrasts to achieve a more accurate simulation of dust‐driven cloud glaciation. Plain Language Summary: Between 0°C and −38°C, clouds can be composed of cloud droplets (water), ice crystals, or some combination of the two. Water clouds reflect much more sunshine back to space compared to ice clouds and therefore have a larger cooling effect on climate. Some atmospheric particles like dust can transform water clouds into ice clouds. The Northern Hemisphere contains more of such particles, which leads to more ice clouds, as confirmed by satellite observations. We such satellite observations to constrain the effect of cloud freezing in climate models and its impact on climate. This helps make climate models and their projections of future climate more realistic. Key Points: Two droplet freezing schemes were assessed using satellite observations of the hemispheric and seasonal contrast in cloud top phase Our results suggest a previous underestimation of dust‐driven droplet freezing, especially for high dust concentrations At midlatitudes, the dust‐driven glaciation with the tuned scheme results in a radiative effect of 0.14 ± 0.13 W m −2